(untitled) (Journal of the College of Basic Education, 2023)
This study was conducted to test the performance efficiency of the semi-fixed sprinkler irrigation system. A factorial experiment was carried out with three lengths of the main system pipe (90, 180, 270 m) and three lengths (60, 120, 180 m) of the system pipe carrying extruders according to the split-piece design (RCBD), where the main length was considered as a main factor, while the sub-length is a sub-factor with three replications. . The uniformity coefficient, the homogeneity coefficient, the addition efficiency and the total efficiency were studied. The study yielded the following results:At the length of 90 m for the main pipe, the highest uniformity coefficient was obtained, as it reached 75.5%, the best uniformity of distribution was 66.7%, the highest addition efficiency was 85.7%, and the best total efficiency of addition was 64.7%. The sub-length of 60 m also excelled in the coefficient of regularity, homogeneity of distribution, efficiency of addition, and total efficiency, reaching 75.56, 65.0, 68.7, and 65.5%, respectively. As for the overlap, the length of 90 and 60 m for each of the main and branch pipes excelled in all the studied characteristics, as this overlap recorded the highest values for each of the uniformity coefficient, distribution homogeneity, addition efficiency, and total efficiency, which amounted to 78, 69, 88, and 68.6%, respectively. The research results showed that there is a highly significant correlation coefficient between the studied field performance characteristics.